BUSINESS MANAGEMENT IN THE FIELD OF TRADE IN THE CONDITIONS OF WAR ON THE BASIS OF INNOVATION - GONCHAR, Olga; DATSUN, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The turbulence of the market environment, the modern challenges of the COVID-19 pandemic and the full-scale war of Russia on the territory of Ukraine determine the need for an innovative search for tools and mechanisms for managing business activities. Entrepreneurship and innovation are the two main factors that ensure economic growth in the conditions of the modern globalization system. In addition to innovative technologies and technological breakthroughs, new methods of market development and labor organization are being introduced. Evaluating the changes taking place in the Ukrainian economy, it is necessary to note that a special role is played by the search and characterization of breakthrough moments, opportunities for innovative development of entrepreneurship, which justify expectations for a new stage of development. The service sector also deserves special attention.The peculiarities of the activity of Ukrainian trade enterprises in war conditions are summarized and attention is focused on the necessary application of innovative tools for their effective activity. The stages of development of innovations at enterprises in the service sector are presented. It is substantiated that the innovative development of trade enterprises should be carried out on the basis of the integration of the innovation management system into the enterprise management system, according to the principles of complexity, dynamism and flexibility, strategic orientation to the formation and development of the enterprise's potential. The future of retail enterprises is assessed. Augmented reality, delivery services, transformation of retail services, Internet services will already be applied to customer service. According to the results of the study, it was concluded that automation and the growth of artificial intelligence are changing the philosophy of trading activities, the key factors in the development of trading enterprises are the qualification of personnel, the intellectual potential of the team, quality, service and balanced resource potential.
Keywords: trade business; trade; innovation; management; organization; efficiency of activity; development